Sulfonated Hypercrosslinked Polystyrene: Synthesis, Characteristics and Use in the Process of Conversion of Fructose to Levulinic Acid - Oleg V. Manaenkov; Olga V. Kislitsa; Evgenia P. Gavrilova; Linda Zh. Nikoshvili; Valentina G. Matveeva (Chemical Engineering Transactions)
Levulinic acid is a precursor to a large number of industrially important chemicals and is widely used in the production of lubricants, chiral reagents, resins, biologically active substances, adsorbents, electronics, and batteries. Levulinic acid is a product of the dehydration of fructose, and acids play an important role in this reaction. High yields of levulinic acid were obtained using sulfuric acid. However, the use of inorganic acids is becoming less attractive, and solid acids may become a viable alternative. A very promising direction in this area is the use of hypercrosslinked polymers, which have many unique properties: large specific surface area, controlled porosity, possibility of modification, exceptional adsorption, chemical and thermal stability, and low cost. This study proposes a method for the synthesis of sulfonated hypercrosslinked polystyrene – SMN270. The synthesized samples were characterized by various methods and tested in the conversion reaction of fructose to levulinic acid. When using SMN270, LA yields of up to 39.5 % were obtained at 180 °C in 1 h with 100 % conversion of the fructose. SMN270 can be an effective replacement for environmentally hazardous mineral acids. The results of the study can become the basis for the creation of stable and efficient solid acid catalysts for the conversion of plant biomass into valuable chemicals.